Buccal transposition flap for closure of maxillary lip defects in 5 dogs. Issue 2 (24th November 2022) - Hildebrandt, Isabella M.; Skinner, Owen T.; Souza, Carlos H. de M.; Karnia, James J.; Reeves, Lauren A.; Mickelson, Megan A.
Abstract: Objective: To describe the technique and outcomes of the closure of maxillary lip defects using a buccal transposition flap and to identify potential routes of vascular supply to the flap. Animals: Five dogs treated clinically and 1 cadaveric dog head. Study design: Short case series and cadaveric study. Methods: A left maxillary labial defect and a buccal transposition flap were created on a cadaver head. Iodinated contrast was injected into the left common carotid artery and computed tomography was performed to assess the vascular supply. Medical records were reviewed for all dogs that underwent tumor excision with maxillary lip resection, reconstructed with a buccal transposition flap. Results: The buccal transposition flap was perfused by branches of the angularis oris artery and superior labial artery. Five dogs were included in this study. All flaps survived. Three dogs developed postoperative complications, including oronasal fistula ( n  = 2) and partial flap dehiscence ( n  = 1). The cosmetic and functional outcomes were considered satisfactory in all cases. Conclusion: Buccal transposition flaps for the closure of large maxillary lip defects provided adequate functional and cosmetic outcomes. The buccal transposition flap had vascular contributions from the angularis oris artery and the superior labial artery.